Investigating the Effect of Climate on National Rice Production using Machine Learning - Rizkyana Rizkyana; Yohana Dewi Lulu (International ABEC, 2021)
This paper examines the influence of climate on national rice productivity using K-Mean Clustering through the Fact Constellation scheme. The research was conducted to see the effect of climate on national rice productivity, especially on the island of Sumatra. For the clustering, the popular machinelearning tool K-Nime was used whose visualization feature was principally useful to determine the patterns, dependencies, and relationships of rice yield on different climate and soil factors of rice production. Research shows that several climateComponents such as temperature, humidity and solar radiation have a very strong influence on national rice productivity.